A NOVEL WEARABLE PUMP-LUNG DEVICE: IN-VITRO AND ACUTE IN-VIVO STUDY - Zhang, Tao (2011)
BACKGROUND: To provide long-term ambulatory cardiopulmonary and respiratory support for adult patients, a novel wearable artificial pump-lung device has been developed. The design features, in-vitro and acute in-vivo performance of this device are reported in this paper. METHODS: This device features a uniquely designed hollow fiber membrane bundle integrated with a magnetically levitated impeller together to form one ultra-compact pump-lung device, which can be placed like current paracorporeal ventricular assist devices to allow ambulatory support. The device is 117 mm in length and 89 mm in diameter and has a priming volume of 115 ml. In-vitro hydrodynamic, gas transfer and biocompatibility experiments were carried out in mock flow loops using ovine blood. Acute in-vivo characterization was conducted in ovine by surgically implanting the device between right atrium and pulmonary artery. RESULTS: The in-vitro results showed that the device with a membrane surface area of 0.8 m(2) was capable of pumping blood from 1 to 4 L/min against a wide range of pressures and transferring oxygen at a rate of up to 180 ml/min at a blood flow of 3.5 L/min. Standard hemolysis tests demonstrated low hemolysis at the targeted operating condition. The acute in-vivo results also confirmed that the device can provide sufficient oxygen transfer with excellent biocompatibility. CONCLUSIONS: Base on the in-vitro and acute in-vivo study, this highly integrated wearable pump-lung device can provide efficient respiratory support with good biocompatibility and it is ready for long-term evaluation.